It will become 61
because anything above 0.5 rounds up
Answer: The constant of proportionality is 1.5
Step-by-step explanation:
The equation for constant of proportionality is y=KX. the K stands for the constant of proportionality and since the constant proportionality is 1.5 you will take 1.5 * x and for example x is 2 so you do 1.5 * 2 and you get 3 and 3 is your y. If you plug in the equation you're saying 3 equals 1.5 * 2 which is right.
Answer:
7/11
Step-by-step explanation:
![- 11 = \frac{ - 7}{y}](https://tex.z-dn.net/?f=%20-%2011%20%3D%20%20%5Cfrac%7B%20-%207%7D%7By%7D%20)
![= > - 11y = - 7](https://tex.z-dn.net/?f=%20%3D%20%20%3E%20%20-%2011y%20%3D%20%20-%207)
![= > y = \frac{ - 7}{ - 11}](https://tex.z-dn.net/?f=%20%3D%20%20%3E%20y%20%3D%20%20%5Cfrac%7B%20-%207%7D%7B%20-%2011%7D%20)
![= > y = \frac{7}{11} (ans)](https://tex.z-dn.net/?f=%20%3D%20%20%3E%20y%20%3D%20%20%5Cfrac%7B7%7D%7B11%7D%20%28ans%29)
Answer: the answer is d trust me
Step-by-step explanation: